(untitled) (New York, 1991)
Contents: 1. Introduction The IT revolution; 2. The information technology platform; 3. The past and present as a window on the future Strategic options 4. Interfirm competition and collaboration,...
Keywords: Organizational change,Thay đổi tổ chức; United States,Hoa Kỳ